PENGARUH GREEN PRODUCT, GREEN ADVERTISING DAN GREEN BRAND TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK TUPPERWARE DI SMPN BEUREUNUEN - PUTRI MAULIZA (LP2MTBM MAKARIOZ, 2020)
The exiting threat on environment has caused many companies ti apply new business concept on environment, called greenmarketing, a concept which includes all marketing activities to stimulate and to maintain consumers’ environmentally friendlybehavior, Some develop countries have applied regulation of green product, clean product in the process of production whichdomestically very significant so that they can compete with foreign products in which supplier,producers and cunsumers canunderstand this concept which has been applied by developed countries. Actually, this concept causes producers to spendmore money, but it has bright future for them. The objective of the research was to find out and to analyze the influence ofgreen product, green advertising, and green brand on decision to buy. Primary data were obtained from 75 respondents withSPSS software program. The result of the research showed that partially, green product, green advertising, and green brandhad positive and significant influence on decision to buy Tupperware product at SMPN Beureuneun. Green product, greenbrand had positive and significant influence on decision to buy Tupperware product at SMPN Beureuneun. Green product,green advertising and green brand simultaneously had the influence on decision to buy product through consumers’ trust atSMPN Beureuneun.